Socialism across the iron curtain : socialist parties in East and West and the reconstruction of Europe after 1945 - Graaf, Jan de (New York : Cambridge University Press, 2018)
"This innovative pan-European history of post-war socialism challenges the East-West paradigm that still dominates accounts of post-war Europe. Jan De Graaf offers a comparative study of the ways in which the French, Italian and Polish Socialist Parties and the Czechoslovak Social Democratic Party dealt with the problems of socio-economic and political reconstruction. Drawing on archival documents in seven languages, De Graaf reveals the profound divide which existed in all four countries between socialist elites and their grassroots as workers reacted hostilely to calls for industrial discipline and for further sacrifices towards the reconstruction effort. He also provides a fresh interpretation of the political weaknesses of socialist parties in post-war continental Europe by stressing the importance of political history and social structure. By placing the attitudes of the continental socialist parties in their proper socio-historical context he highlights the many similarities across and divergences within the two putative blocs"--
"This book could not have been realised without the generous support of various research institutes and funding organisations. First and foremost, I want to thank the Centre for International and European Studies Research at the University of Portsmouth for providing me with a three-year PhD fellowship in 2011. I am also grateful to the German Historical Institute in Warsaw, the Society for the Study of French History, and the British Association for Slavonic and East European Studies for making possible archival sojourns in Poland, France, and the Czech Republic respectively. On a more general level, I would like to express my gratitude to all the staff in the various archives that I visited and to Michael Watson and Elizabeth Friend-Smith at Cambridge University Press"--
Keywords: Socialism -- Europe -- History -- 20th century; Socialist parties -- Europe -- History -- 20th century; HISTORY / Europe / General; Europe, Eastern -- Politics and government -- 20th century; Europe, Western -- Politics and government -- 20th century